PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT SAT NUSAPERSADA TBK - Susanti, Susanti; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2021)
This study aims to analyze the influence of work environment and work discipline toward employee performance of PT Sat Nusapersada Tbk by using saturated sample technique. The method used in this research is quantitative method and data collection technique using questionnaires with 112 respondents of sample sum. All available data were analyzed by SPSS version 25. The results showed the R Square value was 0,548 or 54,8% of the value. It can be seen that the work environment and work discipline variables influenced employee performance by 54,8%, while the remaining 45,2% influenced by other factors. The results of the study based on the t test for work environment has the value 4,541 > 1,98177 and significant value 0,000 < 0,05, which means the work environment variable has a significant effect toward employee performance. The work discipline has the value 3,210 > 1,98177 and significant value 0,002 < 0,05, which means the work discipline variable has a significant effect toward employee performance. The F test result has the value 66,088 > 3,08 and significant value 0,000 < 0,05, which means the work environment and work discipline simultaneously have a positive and significant effect toward employee performance. Keywords: Work Environment; Work Dicipline; Employee Performance.